2020
DOI: 10.1038/s41598-020-72243-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine binding to type III iodothyronine deiodinase

Abstract: Iodothyronine deiodinases (Dios) are important selenoproteins that control the concentration of the active thyroid hormone (TH) triiodothyronine through regioselective deiodination. The X-ray structure of a truncated monomer of Type III Dio (Dio3), which deiodinates TH inner rings through a selenocysteine (Sec) residue, revealed a thioredoxin-fold catalytic domain supplemented with an unstructured Ω-loop. Loop dynamics are driven by interactions of the conserved Trp207 with solvent in multi-microsecond molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Although the biosynthesis of selenocysteine was described as “costly” and “inefficient” [ 9 ], its incorporation into proteins enables living systems to accomplish essential chemical functions that cysteine would not be very good at. The enzymatic activity of mammalian selenoproteins including glutathione peroxidases (GPxs) [ 4 , 10 ], iodothyronine deiodinase [ 11 ], and thioredoxin reductases (TrxRs) [ 12 ] relies on the reactivity of the selenol moiety of a selenocysteine residue [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the biosynthesis of selenocysteine was described as “costly” and “inefficient” [ 9 ], its incorporation into proteins enables living systems to accomplish essential chemical functions that cysteine would not be very good at. The enzymatic activity of mammalian selenoproteins including glutathione peroxidases (GPxs) [ 4 , 10 ], iodothyronine deiodinase [ 11 ], and thioredoxin reductases (TrxRs) [ 12 ] relies on the reactivity of the selenol moiety of a selenocysteine residue [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the crystal structures of Dio1 and Dio2 have not been reported, the previous theoretical study with Dio3-T4 complex revealed that the protonated histidine residue may be involved in the binding of T4 at the active site of Dio3 and a deprotonation resulted in the loss of binding with T4. [13] For the histidine residue at the active site of Dio enzymes, there is another possibility that the imidazole can deprotonate the tyrosine À OH of T4 to make a salt bridge or hydrogen bond between the imidazolinium cation and the phenolate anion, which may disfavour the 5'deiodination.…”
Section: Resultsmentioning
confidence: 99%
“…13 e: Yield: 68 %. 1 H NMR ([D 4 ]MeOH): δ (ppm) 7.90 (s, 2H), 7.22 (s, 2H), 4.86 (s, 2H), 4.30-4.33 (q, 1H), 3.12-3.18 (dd, 1H), 3.26-3.28 (dd, 1H); 13 C NMR (DMSO[D 6 ]): δ (ppm) 33.9, 53.0, 57.9, 91.8, 91.9, 116.0, 125.5, 137.2, 141.1, 151.5, 151.6, 153.4, 170.2 7.90 (s,2H),1H),1H),1H),4.98 (s,2H),1H),J = 7.6 Hz,14.8 Hz,1H),J = 7.6 Hz,14.8 7.89 (s,1H),3H),1H),4.57 (s,2H),1H),J = 7.6 Hz,14.8 Hz,1H),J = 7.6 Hz,14.8 Hz,1H); ESI-MS: m/z calcd for C 17 H 13 I 3 N 2 O 4 : 689.80; found [M + H] + : 690.8088.…”
Section: Synthesis Of O-alkyl Iodothyronine or Iodotyrosinementioning
confidence: 99%
“…Deiodinases (DIOs) are present in target tissues and can amplify or terminate TH signaling through DIO2 and DIO3 ( 38 ). DIO2 converts T4 to bioactive T3, and DIO3 converts both T3 and T4 to diiodothyronine (T2) and reverse T3 (rT3); the latter two are dysfunctional proteins ( 39 ).…”
Section: Effects Of Ths On Bonementioning
confidence: 99%